Dr. Ernesto Galarza Scholarship Symposium Program 2006 - Chicano/Latino Faculty and Staff Association::::::::::::::: (2024)
Program for the 21st Annual Dr. Ernesto Galarza Scholarship Symposium, held at San Jose State University on Tuesday, April 25, 2006 at 5:30 PM – 8:00 PM. The event included a Welcome/Opening Remarks by Dr. Henry Gutierrez (President, CLFSA), Dr. Ana Lomas (Director of Educational Services, Eastside Union School District), and Maria D.L.C. Romo (Chair, Dr. Ernesto Galarza Scholarship Symposium Chair), Presentation of Scholarships by the Dr. Ernesto Galarza Scholarship Committee (Dr. Julia Curry Rodriguez – Chair, Dr. Maria Alaniz, Peggy Cabrera, Dr. Dolores Mena, and Patricia Gutierrez), Keynote Address by Jonathan Alcantar (Dr. Ernesto Galarza Scholarship Recipient), and Closing Remarks by Dr. Henry Gutierrez. Eight awards were presented: Dr. Ernesto Galarza Scholarship, Cesar E. Chavez Scholarship, Simon-Beatriz Scholarship, Jose Antonio Burciaga Scholarship, Castellano Family Foundation Scholarship, Northern California FOCO of the National Association for Chicana/Chicano Studies Scholarship (2 awards), and Marisol Perez Memorial Scholarship.